A Crown Ether Decorated Dibenzocoronene Tetracarboxdiimide Chromophore: Synthesis, Sensing, and Self‐Organization. Issue 1 (15th October 2014) - Ma, Yingjie; Marszalek, Tomasz; Yuan, Zhongyi; Stangenberg, Rene; Pisula, Wojciech; Chen, Long; Müllen, Klaus
Abstract A macrocyclic dibenzocoronene tetracarboxdiimide containing two benzo‐21‐crown‐7 groups has been synthesized. It shows liquid‐crystalline behavior and selectively binds Pb2+ or K+ to form 1:2 complexes in solution. The complexation leads to a significant increase of fluorescence; the surface organization of discotic columnar structures, in the solid‐state, can be controlled by selective ion binding.